2023
DOI: 10.1111/eje.12953
|View full text |Cite
|
Sign up to set email alerts
|

Effect of educational intervention on computer‐aided‐design and computer‐aided‐manufacturing technology to preclinical dental students

Kathleen Fischer,
Michael Metz,
Michael Sekula
et al.

Abstract: IntroductionThis study evaluated the effectiveness of a video presentation instruction compared to the prevailing traditional lecture provided in the preclinical classroom when introducing computer‐aided design/computer‐aided manufacturing (CAD/CAM) technology.Materials and MethodsThis study was conducted as a controlled educational trial (single‐blind) on 120 first‐year dental students. Students were assigned to two learning groups: the control (n = 60, traditional lecture) and the intervention (n = 60, video… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…The other countries in the top six list were consistent across the periods with only the order different among the different periods. The keyword network maps generated in this study identified the emergence of 3D printing, virtual reality, simulation, e-learning, and software during the period between 2019 and 2023, suggesting that the dental education research fraternity is keeping pace with the rapid technological advances in both dentistry and higher education [ 20 , 21 ]. It is also worth noting that the period between 2019 and 2023 had a significant cluster of keywords around COVID-19 that was linked to terms such as burnout, stress, anxiety, and depression, reflecting the trends of uncertainty observed worldwide during the pandemic and, in particular, by the dental fraternity.…”
Section: Reviewmentioning
confidence: 99%
“…The other countries in the top six list were consistent across the periods with only the order different among the different periods. The keyword network maps generated in this study identified the emergence of 3D printing, virtual reality, simulation, e-learning, and software during the period between 2019 and 2023, suggesting that the dental education research fraternity is keeping pace with the rapid technological advances in both dentistry and higher education [ 20 , 21 ]. It is also worth noting that the period between 2019 and 2023 had a significant cluster of keywords around COVID-19 that was linked to terms such as burnout, stress, anxiety, and depression, reflecting the trends of uncertainty observed worldwide during the pandemic and, in particular, by the dental fraternity.…”
Section: Reviewmentioning
confidence: 99%